Assessment of nutritional status and dietary intake of adolescents studying in schools of Kohalpur municipality, Banke district. - Pandey, Madan. (Tufts University. Tisch Library., 2019)
This Poster assess nutritional status and dietary intake of adolescents of school children of Kohalpur Municipality.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy